2018
DOI: 10.1002/bit.26815
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput combinatorial screening reveals interactions between signaling molecules that regulate adult neural stem cell fate

Abstract: Advancing our knowledge of how neural stem cell (NSC) behavior in the adult hippocampus is regulated has implications for elucidating basic mechanisms of learning and memory as well as for neurodegenerative disease therapy. To date, numerous biochemical cues from the endogenous hippocampal NSC niche have been identified as modulators of NSC quiescence, proliferation, and differentiation; however, the complex repertoire of signaling factors within stem cell niches raises the question of how cues act in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Thus, based on study determinations, the gene expression pattern for small molecule hormone receptor interaction between the 2.6 x 10 5 to 2.1 x 10 6 min · count range results in a negative Δ C micro response and an initial downward shift in the contraction with unilateral expansion as compared to positive Δ C micro response with contraction and bidirectional expansion, and irrespective of the specific steriod axis receptor class (ER, AR). Furthermore, it appears that an initial negative (-) Δ C micro response within the 1.86 x 10 6 to 1.94 x 10 6 (IGF-II · IGF-IIR) min · count range is coupled to a positive Δ C micro response, as Dht or R1881 · CM AR (1.79E + 05–2.45E + 05, + P eff ) results in the transcription of pro-proliferative genes [ 118 , 119 ] , that is proposed to be by an initial (-) P eff Χ then an (+) P eff Υ intermediate step coupled to resultant transcriptional activation of MKI67 ( P eff 0.329) [Part I, not cited; 38 ] ( Table 9 ); thus, expression of a focal adhesion or endocytic component may be involved, which would apply to calvarial osteoblasts that overexpress the IGF-IIR/M6P receptor [ 120 ] , and similarly to transformed cells with P eff shift to IGF1R expression [ 121 ] , and could result in altered cell phenotype such as mononucleated: multinucleated [ 5 ] , or lineage commitment such as glial: non-glial during the pre: post exposure period without interaction [ 122 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on study determinations, the gene expression pattern for small molecule hormone receptor interaction between the 2.6 x 10 5 to 2.1 x 10 6 min · count range results in a negative Δ C micro response and an initial downward shift in the contraction with unilateral expansion as compared to positive Δ C micro response with contraction and bidirectional expansion, and irrespective of the specific steriod axis receptor class (ER, AR). Furthermore, it appears that an initial negative (-) Δ C micro response within the 1.86 x 10 6 to 1.94 x 10 6 (IGF-II · IGF-IIR) min · count range is coupled to a positive Δ C micro response, as Dht or R1881 · CM AR (1.79E + 05–2.45E + 05, + P eff ) results in the transcription of pro-proliferative genes [ 118 , 119 ] , that is proposed to be by an initial (-) P eff Χ then an (+) P eff Υ intermediate step coupled to resultant transcriptional activation of MKI67 ( P eff 0.329) [Part I, not cited; 38 ] ( Table 9 ); thus, expression of a focal adhesion or endocytic component may be involved, which would apply to calvarial osteoblasts that overexpress the IGF-IIR/M6P receptor [ 120 ] , and similarly to transformed cells with P eff shift to IGF1R expression [ 121 ] , and could result in altered cell phenotype such as mononucleated: multinucleated [ 5 ] , or lineage commitment such as glial: non-glial during the pre: post exposure period without interaction [ 122 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Nakajima et al [ 163 ] used a cell-based assay to coimmobilize growth factors and natural or synthetic matrices, and they found that EGF promoted the maintenance of NSCs and that two nerve growth factor (NGF) family members, NGF and NT-3, could facilitate NSCs toward neuronal differentiation. In addition to for cell-based microarrays requiring immobilization of biomolecules, Muckom et al [ 177 ] applied a high-throughput microculture system consisting of complementary micropillars and microwells that could hold 532 independent microenvironments for cell culture. They seeded adult rodent NSCs and provided 6 soluble factors, BMP4, TGF-β, FGF-2, shh, Wnt-3a and Ephin-B2, and evaluated the extent to which their individual signals and double, tertiary and quaternary signal combinations could influence neural differentiation[ 177 ].…”
Section: Applications Of Htss To Neurogenesismentioning
confidence: 99%
“…Indeed, presentations from Linda Griffith, Fan Yang and Cole DeForest focused on extracellular matrix components and standardization of the 3D microenvironment (Cambria et al, 2015;DeForest and Tirrell, 2015;Wang et al, 2014), and work presented by Guo-li Ming demonstrated the ability to produce largely identical organoids on a bigger scale (Qian et al, 2016). Patterning was also an area of focus, with Randolph Ashton, Matthias Lutolf, Madeline Lancaster and David Schaffer presenting work on intrinsic and extrinsic cues that control cell fate determination (Knight et al, 2018;Muckom et al, 2018;Ranga et al, 2016).…”
Section: Current Capabilities and Limitations Of In Vitro Modelsmentioning
confidence: 99%